Simple Steps for Synthesis of Silicon Oxide Mesoporous Materials Used as Template - Gautier-Zamora, J; Gautier-Zamora, J; Herrera-Diaz, F; Herrera-Diaz, F; Velez-Cifuentes, J; Arce-Escobar, R; Arce-Escobar, R; Alburquenque-Munoz, D; Alburquenque-Munoz, D; Zuñiga-Loyola, C; Zuñiga-Loyola, C (Sociedad Chilena de Quimica, 2013)
A novel methodology for the synthesis of silicon oxide mesoporous materials has been developed using soft reaction conditions, unlike other synthesis conditions present in the literature. The synthesis involves the use of the lyotropic liquid crystals formed by mixing the surfactant hexadecyltrimethylazanium (CTAB), sodium nitrate as catalyst, water and tetraethyl orthosilicate (TEOS) as the inorganic precursor. The silicon oxide samples were characterized by high-resolution transmission electron microscopy (HRTEM) and EDX analysis. The specific surface area of the powder and the pore size were determined by the BET method and were found to be 587 m2/g and 2-4 nm, respectively. The point of zero charge (pzc) determination using a zeta-meter apparatus was 3. 1 showing the acid character of the surface. The template mesoporous SiO2 samples can be used to prepare composite electrodes containing active mixed oxides, e. g. for lithium-ion batteries.